Fishing in the Forum: Research, Development and Policy Implications for the CPWF - CGIAR Challenge Program on Water and Food (2006)
The First International Forum on Water and Food of the CGIAR Challenge Program on Water and Food (CPWF) was held in Vientiane, Laos from November 12 to 17, 2006. The Forum had two overarching objectives: • to link people together to discover what they are doing within the CPWF and in the world of water and food beyond the Program; • to articulate the links between research, policy and practice.